The psychological aspects of dental students with temporomandibular disorders at Hue University of Medicine and Pharmacy - Nguyen, Gia Kieu Ngan; Vo, Thi To Van; Bach, Ngoc Bao Huy; Nguyen, Hoang Lan; Vo, Duc Huy (Tạp chí Y Dược Huế, 2023)
Background: Psychological factors such as anxiety and depression have been recognized as the etiology of temporomandibular disorders. Objectives: The study aimed to evaluate the prevalence of temporomandibular disorders in dental students and describe the state of depression and anxiety and related factors in the students with the disorders. Materials and methods: 323 students at the Faculty of Odonto-Stomatology, Hue University of Medicine and Pharmacy, were examined to detect temporomandibular disorders, using the DC/TMD axis I. Then GAD-7 and PHQ-9 questionnaires were used to screen for anxiety and depression in the group with the disorders. Results: The proportion of students with temporomandibular disorders was 38.1%, intra-articular disorders accounted for the highest rate (80.5%). The percentages of depression and anxiety among students with the disorder were 28.4% and 55.3%, respectively. 41.5% of TMD students had mild anxiety and the same proportion of students had risk of depression. Risk factors associated with depression and anxiety were economic status and excercise, respectively (p < 0.05). Conclusions: The percentage of students with temporomandibular disorders is relatively high. The majority of students with the disorders are at risk for depression and low level of anxiety. There is a link between the economic status and depression, between exercise and anxiety.